Scalable focused ion beam creation of nearly lifetime-limited single quantum emitters in diamond nanostructures - Tim Schröder (Nature Portfolio, 2017)
Interfacing spin quantum memories with photons requires the controlled creation of defect centre—nanocavity systems. Here the authors demonstrate direct, maskless creation of single silicon vacancy centres in diamond nanostructures, and report linewidths comparable to naturally occurring centres